Challenges of Freshwater Fisheries in Nepal: A Short Overview - Gautam, Nawaraj (International Journal of Applied Sciences and Biotechnology, 2015)
Abundant freshwater resources originated from Himalayas and high geographical variations in Nepal are two factors which might be positive benefits to improve the aquaculture in land locked country. Low labor cost is also another plus point to get better management in fisheries sector. Freshwater fisheries in Nepal are mostly dominated by catch up fisheries of indigenous fish species available in rivers, lakes and paddy fields but exotic and sophisticated species been also introduced in small scales. Beside these, poly cultural pond fish farming is most viable. Carp fishes are the major species and uncontrolled unmanaged capture fisheries dominants over systematic aquaculture. Poor technological implementations, poor budgetary plan, not proper management strategies, lack of quality fish feed and fingerlins, lower market availability are some of the major challenges of Nepalese freshwater fisheries. Long-term sustainable plan, scientific and technological study on indigenous fish species, proper hygiene management and better disease control might improve the current aquaculture status of Nepal. Int J Appl Sci Biotechnol, Vol 3(4): 579-583